2008
DOI: 10.1111/j.1572-0241.2008.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Rising Prevalence of Venous Thromboembolism and Its Impact on Mortality Among Hospitalized Inflammatory Bowel Disease Patients

Abstract: VTE is increasingly prevalent among hospitalized IBD patients and has substantial mortality and economic impact. These findings drive the need for widespread prophylaxis against and early detection of VTE among IBD inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
263
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(287 citation statements)
references
References 28 publications
14
263
2
8
Order By: Relevance
“…Although heparin no longer warrants consideration as primary therapy for UC ( 266 ), it has an important role in prophylaxis against thromboembolism in patients admitted to hospital with severe colitis ( 267 ). For the patient with a series of thrombotic or embolic events during a course of severe colitis, emergent colectomy may be lifesaving in preventing additional, potentially fatal thrombi.…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…Although heparin no longer warrants consideration as primary therapy for UC ( 266 ), it has an important role in prophylaxis against thromboembolism in patients admitted to hospital with severe colitis ( 267 ). For the patient with a series of thrombotic or embolic events during a course of severe colitis, emergent colectomy may be lifesaving in preventing additional, potentially fatal thrombi.…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…Inflammatory bowel disease has been shown to be associated with a 1.5-to 3.6-fold increased risk for VT. [50][51][52] In one cohort study from Canada, risks for DVT and PE were presented separately. The IRR was 4.7 (95% CI, 3.5-6.3) for DVT and 2.9 (95% CI, 1.8-4.7) for PE in Crohn disease and 2.8 (95% CI, 2.1-3.7) for DVT and 3.6 (95% CI, 2.5-5.2) for PE, in ulcerative colitis.…”
Section: Chronic Acquired Risk Factorsmentioning
confidence: 99%
“…age group, for both UC and CD throughout the study period. Prior studies have shown race-specific differences in utilization of surgery as well as disease manifestations and complications in IBD patients [4][5][6][7][8]. Age-specific changes in hospitalizations were not found in one prior study [2], but were found to peak during earlier years in CD patients in another [3].…”
mentioning
confidence: 78%